1992
DOI: 10.1002/anie.199207681
|View full text |Cite
|
Sign up to set email alerts
|

A New Reaction Type in the Conversion of Enamines with 1,4‐Diphenyl‐2‐butene‐1,4‐dione to Give Cage Compounds

Abstract: Mn-N bond lengths (2.406(4) A). As expected with a higher coordination number, Mn to ligand bonds are considerable longer than those of six-coordinate Mn" complexes, but are similar to those found in the square-antiprismatic complex, [Mn(cyclen),12 + (2.384-2. 435 (cyclen = 1,4,7,10-tetraazacyclododecane). The only other examples of discrete bipyridine-N,N'-dioxide) and (Et,N),~(NCS),]. ["] The great flexibility of the [2. 6.872 A in the empty ~r y p t a n d . [~~~ The metal has induced a twisting of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Thus, it was shown that the interaction of cyclic enamines 21 a-d with dibenzoylacetylene 22 leads to the formation of bicyclic cyclobutene derivatives 23 a-d, which, except for 23 a, instantly isomerize to monocyclic 1,3-dienes 24 b-d (Scheme 7). [11] For further convenience of presenting the material, we depicted frequently used enamines in this review in Figure 2.…”
Section: Four-membered Carbocyclesmentioning
confidence: 99%
“…Thus, it was shown that the interaction of cyclic enamines 21 a-d with dibenzoylacetylene 22 leads to the formation of bicyclic cyclobutene derivatives 23 a-d, which, except for 23 a, instantly isomerize to monocyclic 1,3-dienes 24 b-d (Scheme 7). [11] For further convenience of presenting the material, we depicted frequently used enamines in this review in Figure 2.…”
Section: Four-membered Carbocyclesmentioning
confidence: 99%